Backchannel as a Listener’s Consideration Behavior: Politeness Strategy of Japanese Native Speakers in Interaction - Lisda Nurjaleka (Universitas Sanata Dharma, 2021)
Japanese tend to deliver backchannel for being supportive and representing people’s interest in their interaction. Many linguists believed Backchannel as discourse markers that showed interlocutors’ negative faces and determined their social hierarchy position. Brown and Levinson’s (henceforth BL) politeness theory has been modified, criticized, and applied to all languages globally. This research aims to know whether the BL politeness theory can explain Backchannel as a consideration behavior. Furthermore, we investigate the position, situation, and the relation between the speaker listener in a conversation. The primary data are a data corpus of 30 minutes’ length of 15 natural conversations. The age of the target is between the ‘20s to ‘40s. We also compare and analyze the situation from a first-timer conversation, a conversation between friends, and a hierarchical relationship. This study will help understand the relation between speaker and listener or whether Backchannel is considered a consideration behavior. Consideration is one act to shows politeness to the interlocutors. The result shows that Japanese people use different Backchannel according to the partner he/she speaks. When the interlocutors meet for the first time or have a higher position, they mostly use the polite form. They also consider the relationship, the interlocutor's gender, and age. This finding shows that the Japanese use Backchannel as a consideration to maintain the interlocutor's face.